„Dziki Zachód” Państwa Środka – bezpieczeństwo i gospodarka w chińskiej polityce wobec prowincji Xinjiang - Mikołajczyk, Szymon (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The main purpose of the article is to present the key elements of Chinese policy in Xinjiang. This western province represents 1/6 of China’s landmass and plays a significant role in Chinese security and economic policy. This study tries to show the complexity of challenges that Chinese have to face in their attitude to Xinjiang. For years, Xinjiang was known as a primary front in Chinese war on terrorism. That is why, a question whether the government uses the threat of terrorism as an excuse to violate minority rights is raised. Recently, China has been implementing a new policy, which is more concerned on economic development and improvement of living standards and could be a first step in a long way to stabilize the situation in the province.